POLITICAL COMMUNICATION DYNAMICS IN LEGISLATIVE ELECTION 2014 IN NORTH ACEH REGENCY - Fauzi, Fauzi; Marhamah, Marhamah; Rahmani, Shafira Ulfa (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2021)
This study aims to describe the credibility of political communicators and political messages in the 2014 Legislative Election in North Aceh Regency. This study used descriptive qualitative method. Data collection techniques were carried out through interviews, observation and documentation. The results showed that the credibility of political communicators in the 2014 Legislative Election in North Aceh Regency was reflected in the public's trust in the capabilities of legislative candidates. The public's trust is based on the image of the legislative candidate who is a figure or figure who is already known and liked by the community. And political messages in the 2014 Legislative Election in North Aceh Regency were conveyed using mass media, both print media, electronic media, banners or billboards and online media. Political messages are verbal and nonverbal messages in the form of political information and advertisements.